Implementation of project-based learning in assessing the creativity abilities of prospective biology teachers - Mia Nurkanti; Cita Tresnawati; Fitri Aryanti; Yusuf Ibrahim (Universitas Muhammadiyah Malang, 2024)
Developing the 21st century abilities is a challenge for educational institutions, especially when it comes to learning that encourages students to be creative. The purpose of this study is to evaluate the creative capacities of prospective biology teacher students by implementing Project-Based Learning (PjBL) in nutrition science subjects. Performance observation sheets and portfolios were employed in this study, which involved 40 students of biology education at a private educational institution in Bandung. This study used an experimental class by first determining the criteria for the percentage of at least 70%. The results of the study show that the percentage with an average value of 51.80% is included in the sufficient category but is still below the specified average standard. The novelty indicator is 50.65% in the sufficient category the useful indicator is 39.53%, the effect on others is 22.30% and the ability to generalize is 31.53% which is still in the less category. Based on this, overall student creativity after the implementation of PjBL learning in the Nutrition Science course still needs to be improved. Findings of learning using PjBL are able to positively correlate with increasing student learning motivation and independence.